Germline Mutations in Predisposition Genes in Pediatric Cancer - Zhang, Jinghui; Walsh, Michael F; Wu, Gang; Edmonson, Michael N; Gruber, Tanja A; Easton, John; Hedges, Dale; Ma, Xiaotu; Zhou, Xin; Yergeau, Donald A; Wilkinson, Mark R; Vadodaria, Bhavin; et al. (The New England journal of medicine, 2015)
A constitutive mutation in a cancer-susceptibility gene can have implications for clinical treatment and genetic counseling of family members. This study involving 1120 children and adolescents showed that 95 (8.5%) had such a mutation. The frequency of germline mutations in cancer-predisposition genes in children and adolescents with cancer and the implications of such mutations are largely unknown. Previous studies have relied mainly on candidate-gene approaches, which are, by design, limited. To better determine the contribution of germline predisposition mutations to childhood cancer, we used next-generation sequencing, including whole-genome and whole-exome sequencing, to analyze the genomes of 1120 children and adolescents with cancer. We describe the prevalence and spectrum of germline variants among 565 cancer-associated genes, with an emphasis on the analysis of 60 genes that have been associated with autosomal dominant cancer-predisposition syndromes. We . . .